2007
DOI: 10.1111/j.1365-2095.2007.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein-sparing effect of carbohydrate in silver barb, Puntius gonionotus fry

Abstract: A 30-day study was undertaken to examine the proteinsparing effect of carbohydrate in diets for silver barb, Puntius gonionotus fry. Six semi-purified experimental diets were formulated with two levels of protein (200 and 250 g kg )1 diet) and three levels of carbohydrate (300, 340 and 380 g kg )1 diet). In addition to the six experimental diets, a diet containing the protein and carbohydrate requirement levels of 300 and 260 g kg )1 diet, respectively, as reported earlier for this species, was used as a refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
61
2
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 31 publications
12
61
2
3
Order By: Relevance
“…accumulation in the fish body as a result of de novo synthesis of fatty acids, similarly to other findings, which also resulted in reduced lipid deposition(Gao et al, 2010;Mohanta et al, 2007;Nijhof and Bult, 1994). In addition, our results suggest that when dietary lipid was supplied in excess(> 16.8%), a proportion of the dietary lipid may have been deposited as lipid and not glycogen in the body.…”
supporting
confidence: 83%
“…accumulation in the fish body as a result of de novo synthesis of fatty acids, similarly to other findings, which also resulted in reduced lipid deposition(Gao et al, 2010;Mohanta et al, 2007;Nijhof and Bult, 1994). In addition, our results suggest that when dietary lipid was supplied in excess(> 16.8%), a proportion of the dietary lipid may have been deposited as lipid and not glycogen in the body.…”
supporting
confidence: 83%
“…FCR, SGR and PER also significantly improved with decrease in protein content from 40 to 30% and with the increase in dextrin from 30 to 40%. Mohanta et al. (2007) observed that dietary protein could be reduced from 30 to 25% in the diet by increasing carbohydrate from 26 to 34% without compromising growth of silver barb, Puntius gonionotus , fry.…”
Section: Discussionmentioning
confidence: 99%
“…In carp, carbohydrates seem to compete successfully with lipids as an energy source (Takeuchi et al., 1979; Dabrowski, 1986). Although a protein‐sparing effect induced by dietary carbohydrates has been extensively reported for many species (Degani and Viola, 1987; Shiau and Lin, 1993, 2001; Seenappa and Devaraj, 1995; Martino et al., 2005; Ovie et al., 2005; Singh et al., 2006; Abimorad and Carneiro, 2007; Mohanta et al., 2007), information on L. rohita is scarce and the results are not consistent (Erfanullah and Jafri, 1995, 1998; Satpathy and Ray, 1998; Saha and Ray, 2001; Dalal et al., 2002). In the present study, a 4 × 3 factorial designed study including four dietary protein levels (25, 35, 40 and 45%) and three dietary dextrin levels (15, 25 and 35%) was undertaken to evaluate their effects on growth, nutrient utilization, body composition and protein‐sparing effect of carbohydrate in fingerling rohu, Labeo rohita .…”
Section: Introductionmentioning
confidence: 99%
“…Though diet 3 (rice bran-based diet) performed well, Diet 1(WB-based diet) demonstrated the best growth because the crude fibre levels were lower. In addition, the NFE a measure of the carbohydrate level in diets (Mohanta et al, 2007;Tran-Duy et al, 2008) was higher in Diet 1 than in Diet 3 suggesting a greater the protein sparing effect (that is, the use of carbohydrate to spare the use of protein for energy purposes). This is because, more energy in the form of NFE was available in Diet 1 than it is in Diet 3 to spare the use of protein as an energy source.…”
Section: Growth Performance Of Fingerlings O Niloticusmentioning
confidence: 99%